1973
DOI: 10.1017/s0022172400023020
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the microbial flora in the air of submarines and the nasopharyngeal flora of the crew

Abstract: SUMMARYAirborne bacteria surveys in nuclear submarines show that the total microbial load was maintained at satisfactorily low levels during prolonged patrols despite factors which were expected to increase this form of pollution.The isolation rates of Staphylococcus aureus and Neisseria meningitidis from nasal and nasopharyngeal swabs respectively, together with the serum antibody titres to Mycoplasma pneumoniae, before and after patrols suggested that the transmission of these organisms between individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Other studies have been performed on isolated men in space flights and space flight simulators for relatively short periods (Carmichael & Taylor, 1977;Taylor & Zaloguev, 1976) and in submarines (Morris & Fallon, 1973) for longer periods. In none of these studies has the effect of interfering with the bacterial flora been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have been performed on isolated men in space flights and space flight simulators for relatively short periods (Carmichael & Taylor, 1977;Taylor & Zaloguev, 1976) and in submarines (Morris & Fallon, 1973) for longer periods. In none of these studies has the effect of interfering with the bacterial flora been studied.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In a submarine, aerosolised transmission is also possible. 12 Despite the high frequency of skin disorders in the submarine environment, few studies linking this to S. aureus carriage have been carried out; a study performed in the early 1970s indicated that, similar to civilian populations, S. aureus carriage rates in submariners are about 30%. 12 …”
Section: Introductionmentioning
confidence: 99%